Reducing Sleep Disturbance by Using Slow Deep Breathing and Dhikr in Cancer Patients During Chemotherapy - Fahrun Nur Rosyid; Beti Kristinawati; Nurlaila Fitriani; Sugiyarti; Ahmad Fadhlur Rahman (Nusantara Science and Technology Proceedings)
This study aims to investigate the effects of slow deep breathing (SDP) and dhikr on sleep disturbance in cancer patients during chemotherapy. This study used a Quasi-experiment design. A total of 44 cancer patients experiencing chemotherapy who met the inclusion criteria were divided into 2 groups of 22 patients. The treatment group practiced SDB and dhikr, while the control group practiced normal breathing. This intervention was performed for 30 minutes and repeated for 3 cycles of chemotherapy. Furthermore, sleep disturbance is measured by the Pittsburgh Sleep Quality Index sheet. The data is analyzed using the Paired t-test, independent t-test, and Chi-square test with a significance limit of p <0.05. The result after 3 treatment cycles, sleep disturbances decreased in the treatment group from 7.64 ± 2.19 to 6.73 ± 1.78 or decreased by 0.91 ± 1.54, but in the control group, there was an increase from 5.00 ± 1 .90 to 5.18 ± 1.99 or an increase of 0.18 ± 0.85. The analysis results of SDP and dhikr effect on sleep disturbance in cancer patients during chemotherapy is significant (p=0.010). This study concludes SDB, and Dhikr can reduce sleep disturbance in cancer patients during chemotherapy.